2023
DOI: 10.1177/19253621231157504
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Imaging Detected Silent Male Breast Cancer in Autopsy Specimens: Study of the Disease Held by Image-Guided Biopsies

Abstract: Introduction: Regarding male breast cancer, a rare disease comprising ∼1% of breast cancers, data are generally scant. The present study aimed to quantify the imaging detected breast cancer in male gender corpses, determining in this way the prevalence of silent breast cancer in male gender. Methodology: The population target has been male corpses without clinical expression of breast cancer. Seventy-four male corpses have been submitted to bilateral subcutaneous radical mastectomy. Samples have been submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 122 124 In contrast to the above studies, it is also reported that on comparison with women, men have a slightly better or equivalent disease-specific survival. 125 , 126 …”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%
“… 122 124 In contrast to the above studies, it is also reported that on comparison with women, men have a slightly better or equivalent disease-specific survival. 125 , 126 …”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%